Real-time vision, tactile cues, and visual form agnosia: removing haptic feedback from a “natural” grasping task induces pantomime-like grasps - Whitwell, Robert L.; Ganel, Tzvi; Byrne, Caitlin M.; Goodale, Melvyn A. (Frontiers in Human Neuroscience, 2015)
Investigators study the kinematics of grasping movements (prehension) under a variety of conditions to probe visuomotor function in normal and brain-damaged individuals. When patient DF, who suffers from visual form agnosia, performs natural grasps, her in-flight hand aperture is scaled to the widths of targets ('grip scaling') that she cannot discriminate amongst. In contrast, when DF's pantomime grasps are based on a memory of a previewed object, her grip scaling is very poor. Her failure on this task has been interpreted as additional support for the dissociation between the use of object vision for action and object vision for perception. Curiously, however, when DF directs her pantomimed grasps towards a displaced imagined copy of a visible object where her fingers make contact with the surface of the table, her grip scaling does not appear to be particularly poor. In the first of two experiments, we revisit this previous work and show that her grip scaling in this real-time pantomime grasping task does not differ from controls, suggesting that terminal tactile feedback from a proxy of the target can maintain DF's grip scaling. In a second experiment with healthy participants, we tested a recent variant of a grasping task in which no tactile feedback is available (i.e. no haptic feedback) by comparing the kinematics of target-directed grasps with and without haptic feedback to those of real-time pantomime grasps without haptic feedback. Compared to natural grasps, removing haptic feedback increased RT, slowed the velocity of the reach, reduced grip aperture, sharpened the slopes relating grip aperture to target width, and reduced the final grip aperture. All of these effects were also observed in the pantomime grasping task. Taken together, these results provide compelling support for the view that removing haptic feedback induces a switch from real-time visual control to one that depends more on visual perception and cognitive supervision.